PEMBUATAN DAN KARAKTERISASI MATERIAL KOMPOSIT SERAT IJUK (Arenga pinnata) SEBAGAI BAHAN BAKU COVER BODY SEPEDA MOTOR - Achmad Kusairi Samlawi; Yulian Firmana Arifin; Pandu Yuda Permana (INFO-TEKNIK, 2017)
The purpose of this research is to know the influence of composition of mass fraction between filler and matrix to mechanical strength of composite material utilizing fibers fiber (arenga pinnata) as filler with polyester resin matrix, composition of fiber fraction mass and polyester resin is 30%:70%, 40%: 60% and 50%: 50% with fiber angle orientation: 0; 0; 0; 0, using the Hand Lay Up making composite methode. Impact test is done with ASTM D5942-96 standard and Tensile Testing is done with ASTM D638-03 standard. Impact test results show that all composition of mass fraction have value Energy impact above Energy impact Cover Body Motorcycle Brand X used as comparative material, 50%: 50% mass fraction composition yield the highest impact energy value equal to 198,75 Joule / cm2. Tensile Test showed the composition of mass fraction 50%: 50% yield value of tensile strength equal to 27,09 MPa is the value of tensile strength most closely to value of tensile strength of comparative material of 30,24 MPa, Tensile Test also shows all composition of mass fraction have the percentage of length increase above the percentage of comparative material, the composition of 50%: 50% mass fraction yields the highest percentage of 4.02%. This research concludes that fiber composite material (arenga pinnata) with 50%: 50% mass fraction composition is feasible to be used as an alternative material Cover Body Motorcycles.